Terrestrosin D, a spirostanol saponin from Tribulus terrestris L. with potential hepatorenal toxicity. (30th January 2022) - Sun, Xiao-Chen; Song, Xiao; Guo, Fei; Yuan, Yao-Hui; Wang, Shu-Yue; Wang, Shuai; Liu, Kun-Lin; Lv, Xi-Yu; Han, Bing; Zhang, Chao; Liu, Jiang-Ting
Abstract: Ethnopharmacological relevance: Fructus Tribuli (FT) has been commonly used as a traditional medicine for thousands of years. With the diverse uses of FT, more attention has been paid to its hepatorenal toxicity. However, the compounds causing the hepatorenal toxicity of FT remain undetermined. Terrestrosin D (TED), a major spirostanol saponin isolated from FT, may exert hepatorenal toxicity. Aim of the study: This study aimed to evaluate the potential hepatorenal toxicity of TED, and preliminarily explore the possible mechanism of TED-induced hepatorenal toxicity. Materials and methods: Cytotoxicity assays, a repeated-dose 28-day in-vivo study, a toxicokinetic study, and a tissue distribution study were used to evaluate the potential hepatorenal toxicity of TED. Furthermore, network pharmacology was applied to preliminarily explore the possible mechanism of TED-induced hepatorenal toxicity. Results: Both the in vitro and in vivo studies showed that the spirostanol saponin TED had potential hepatorenal toxicity. Nonetheless, hepatorenal toxicity induced by oral treatment with TED at a dosage range of 5 – 15 mg/kg daily for 28 consecutive days to Sprague-Dawley (SD) rats was reversible after 14 days of TED withdrawal. The toxicokinetic study demonstrated that the systematic exposure of SD rats to TED had an accumulation phenomenon and a dose-dependent trend after a 28-day repeated-dose oral administration. The tissue distribution study revealed that TED had a targeted distribution in the liver and kidneys accompanied by a phenomenon of accumulation in SD rats. Network pharmacology combined with molecular docking methods was used to screen for the key targets (HSP90AA1, CNR1, and DRD2) and the key pathways of TED-induced hepatorenal toxicity. Conclusions: The spirostanol saponin TED, a major spirostanol saponin isolated from FT, had potential hepatorenal toxicity. Graphical abstract: Image 1